Test–Retest Reliability of Task-Oriented Strength and Object Position in a Box Lifting Task Using the Activities of Daily Living Test and Training Device (ADL-TTD) in Children with Unilateral Spastic Cerebral Palsy. - Guo, Haowei; Heus, Inge; Snijders, Bart; Land, Nanne E.; van der Holst, Menno; Smeets, Rob. J. E. M.; Bastiaenen, Caroline H. G.; Rameckers, Eugene A. A. (Children, 2025)
Purpose: This study investigates the test–retest reliability of maximal voluntary contraction (MVC) and integrated object positioning during bimanual box lifting tasks in children with unilateral spastic cerebral palsy (USCP), using the Activities of Daily Living Test and Training Device (ADL-TTD). Materials and Methods: Utilizing an explorative cross-sectional design, the study recruited 47 children with USCP. The ADL-TTD, equipped with an Inertial Measurement Unit (IMU) for precise object positioning, measured MVC, and object position in 3D space in a cross-sectional measurement containing two measurements in a fixed time period. Results: The findings demonstrated good test–retest reliability for MVC, with an ICCagreement of 0.95 for the mean MVC value. Additionally, good reliability was observed for object positioning in different directions measured with an IMU, with ICCagreement ranging from 0.82 to 0.86 degrees. Regarding the standard error of measurement (SEM), the SEMagreement for the mean MVC value was 5.94 kg, while the SEMagreement for object positioning was 1.48, 5.39, and 3.43 degrees, respectively. Conclusions: These results indicate that the ADL-TTD demonstrates good test–retest reliability for both MVC and object positioning, making it a valuable tool for analyzing this population in cross-sectional research by providing reliable measures of task-oriented strength and object manipulation. However, the relatively high SEMagreement, particularly in MVC, suggests that caution is needed when using this tool for repeated testing over time. This pioneering approach could significantly contribute to tailored assessment and training for children with USCP, highlighting the importance of integrating task-specific strength and positional accuracy into therapeutic interventions.